2015
DOI: 10.1007/s10811-015-0633-2
|View full text |Cite
|
Sign up to set email alerts
|

Selection of yeast strains for bioethanol production from UK seaweeds

Abstract: Macroalgae (seaweeds) are a promising feedstock for the production of third generation bioethanol, since they have high carbohydrate contents, contain little or no lignin and are available in abundance. However, seaweeds typically contain a more diverse array of monomeric sugars than are commonly present in feedstocks derived from lignocellulosic material which are currently used for bioethanol production. Hence, identification of a suitable fermentative microorganism that can utilise the principal sugars rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 43 publications
2
44
1
Order By: Relevance
“…Algal polysaccharide composition is often different from that of terrestrial plants with the most important polysaccharides of brown algae being Laminarin, Mannitol, Alginate and Fucoidan [151]. Algae can also typically contain a more diverse range of monomeric sugars than terrestrial plants [152]. Algal polysaccharides are further discussed in Section 5.3.…”
Section: Algaementioning
confidence: 99%
“…Algal polysaccharide composition is often different from that of terrestrial plants with the most important polysaccharides of brown algae being Laminarin, Mannitol, Alginate and Fucoidan [151]. Algae can also typically contain a more diverse range of monomeric sugars than terrestrial plants [152]. Algal polysaccharides are further discussed in Section 5.3.…”
Section: Algaementioning
confidence: 99%
“…The total carbohydrates fraction in seaweeds and most biomass are made up of various monomeric sugars (reducing sugars). Seaweeds are known to be composed of a broad diversity of monomeric sugars or monosaccharides as compared to other biomass such as cassava, sugarcane and elephant grass used in bioethanol production [28]. This study found the major monomeric sugars in U. fasciata to be glucose, xylose and rhamnose at 15.1, 7.6 and 5.4%, respectively; S. vulgare had glucose and fucose at 15.3 and 4.0%, respectively; and H. dentata had galactose and glucose at 13.1 and 12.0%, respectively, of dry biomass (Table 3).…”
Section: Monomeric Sugar Composition Of the Selected Seaweedsmentioning
confidence: 99%
“…The genomic integration and overexpression of the gene encoding alginate monomer (4‐deoxy‐ l ‐erythro‐5‐hexoseulose uronate) transporter from the alginolytic eukaryote Asteromyces cruciatus enabled S. cerevisiae to ferment this monomer and produce bioethanol (Enquist‐Newman et al, ). For the screening and selection of yeast strains capable to metabolize a range of monosaccharides originating from the breakdown of macroalgal polysaccharides, a phenotypic microarray (metabolic output of yeast strains grown on synthetic minimal media with different carbon sources) can be applied (Kostas et al, ). An interesting study was presented by Khambhaty et al () who proposed for the first time the isolation, characterization and utilization of marine yeast ( Candida sp.)…”
Section: Technologies Converting Algal Biomass To Energymentioning
confidence: 99%